THE CRITIQUES AND IDEOLOGIES SHARED IN THE INAUGURATION SPEECH OF DONALD TRUMP (A STUDY OF CRITICAL DISCOURSE ANALYSIS) - Imron Hizbullah; Muhammad taufiq Al Makmun (Jurnal Bahasa, Sastra, dan Studi Amerika, 2019)
This paper investigates the Critical Discourse Analysis (CDA) in studying the inauguration speech of Donald Trump at the Capitol Hill, Washington DC on January 20, 2017. The objective of the study is to uncover the hidden messages regarding ideologies shared and critiques appointed to Obama’s presidency. The paper uses the theory of CDA by Norman Fairclough by focusing on the three aspects of research which are (1) micro or linguistic analysis, (2) Mezzo or discursive analysis, and (3) macro or contextual analysis. The three dimensional model of CDA is aimed to uncover the ideologies shared and critiques appointed to based on linguistic features, socio-political aspect, and discursive practice. The American Dream is represented in seven issues risen which are (1) US economic condition during Obama’s presidency, (2) US political condition during Obama’s presidency, (3) US social condition during Obama’s presidency, (4) The concept of making America great again, (5) Anti-radical Muslim immigrants, (6) America First, and (7) Nationalism. The result of the study reveals that the speech brought some ideologies or thoughts shared to the audiences and might change the people’s perception on Obama’s two periods of presidency who is considered as failure.